Development and validation of a risk perception scale on acute respiratory infections for caregivers in long-term care facilities - Zhihao Xie; Jiayi Zhu; Xiaofeng Xie; Lei Huang; Jianhua Ren; Jianhua Ren; Ruben Martin-Payo; Ruben Martin-Payo; Mengying Qiu; Fengying Zhang (Frontiers in Public Health)
IntroductionAcute respiratory infections (ARIs) represent a significant threat to global public health, particularly among older adults residing in long-term care facilities (LTCFs), where high-density living conditions facilitate the rapid transmission of infections. The perception of risk regarding ARIs among caregivers is critical, as it directly influences their protective behaviors and decision-making during epidemic outbreaks. Despite the importance of this perception, there is currently no validated instrument specifically designed to assess caregivers’ risk perception of ARIs within the context of LTCFs. This study aims to address this gap by developing a reliable and accessible scale to measure caregivers’ risk perception.MethodsWe developed an initial scale through a comprehensive literature review and two rounds of Delphi consultations with 19 experts in related field. A total of 428 participants in LTCFs were surveyed, yielding 343 valid responses and efficiency rate of 80.14%. Following a systematic scale development process that encompassed pretest, item analysis, and exploratory factor analysis (EFA) involving 123 respondents, we refined the scale to its robustness. Confirmatory factor analysis (CFA) was conducted with an additional 220 participants, alongside rigorous tests for reliability, stability, and validity, to evaluate the final scale.ResultsThe developed scale consists of nine items categorized into three dimensions: severity, controllability, and susceptibility, all of which meet essential criteria for reliability and validity. The overall Cronbach’α coefficients for the scale was 0.795, with each dimension coefficient of 0.795, 0.707, and 0.791, respectively.DiscussionIn its current form, this scale serves as a valuable tool for managers and practitioners, enabling them to preliminarily assess caregivers’ risk perceptions regarding ARIs in LTCFs. By enhancing our understanding of caregivers’ behaviors, this instrument has the potential to inform targeted interventions.